TEACHING FOREIGN LANGUAGES AND MEDICAL PRACTICE LET'S GO PROJECT: A HUMANIZED PERSPECTIVE - Rocha, Nildiceia Aparecida [UNESP]; Thereza Weber, Silke Anna [UNESP]; Carvalho, Larissa Pierri [UNESP]; Fonseca, Eduardo [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2017)
Society today is increasingly characterized by cognitive work and, in the context of globalization, a foreign language (FL) is the first barrier that must be overcome to the to the insertion of an individual at a national and international level. An important facilitator to the learning of a second language is the early introduction of a FL (Brown, 2001), making use of child's natural curiosity to introduce them in to the study of another language. For that, the teacher needs to work his skill to transmit knowledge in a more comprehensible way, improving an essential skill for a future doctor, assuming a more humanized posture. In that way, this study focus on the experiences that medical students undergo as promoters of the learning of English for students of the 5th year of the Elementary School, through the extension project Let's Go. This project aims to awaken in children the interest for a FL as well as to interface the students of the Faculty of Medicine of Botucatu with children from a different social context, developing their interpersonal and communication skills. As method, a brochure was produced by the medical students under the supervision and orientation of languages and medicine professors. The brochure is used as material to English classes once a week to 90 children of three classes of the 5th year of the Elementary School of two public schools. In order to evaluate the course, a questionnaire was elaborated and applied at the beginning and at the end of the school year. It is observed that, in general terms, through the analysis of the questionnaires, that the project Let's Go is achieving its objectives: to promote and encourage the learning of English, as well as to interact medical students of the Faculty of Medicine of Botucatu with the community in a humanized perspective.
Keywords: Teaching foreign languages; Medical practice; Humanized approach